Deformation and fracture of high-temperature steels at different temperatures and loading rates - Kondryakov, E.A.; Lenzion, S.V.; Kharchenko, V.V. (Проблемы прочности, 2009)
Charpy impact tests were conducted at different temperatures and loading rates. Temperature dependences of the crack initiation and propagation energies were determinedfor carbon steel 45, steels St. 3 and 15Kh2NMFA from the load-time curves obtained with due account of the impact test results. The effect o f the loading rate on the temperature dependence o f the impact toughness was analyzed within the range from 1 to 4.4 m/s.